The relevancy of law enforcement toward water quality in Kali Buntung’s downstream area - Gunawan Lisa Elizabeth (EDP Sciences, 2021)
Kali Buntung actually is a man-made afvoer river. However, due to city development, the location now become a strategic asset for Sidoarjo Region. Due to that reason, this river experience external forces such as rapid land conversion, social, law enforcement, upstream quality, rainfall and surrounding businesses that make the rivers’ burden much heavier. This paper aims to investigate the external forces matters and the calculating the impact of those external forces towards the water quality in Kali Buntung’s downstream area. Using Structural Equation Model (SEM) as the basis to produce such intended result, the indicator data will be processed using SMART PLS statistic software. The result of this research was: (1) the upstream water quality is very significant with the water quality in downstream. (2) rainfall have a significant effect toward upstream water’s revitalization process along the way the water flows toward the downstream. (3) social and business aspects have significant influence to the water quality in downstream. (4) law enforcement has positive impact on downstream’s water quality, even surpass either the rainfall or business factors. (5) the law enforcement to businesses may reward greater impact than to the common inhabitant surrounding. (6) since land conversion is inevitable, law enforcement might be the only way to keep enjoying the favorable impact of business capability and agriculture field to reduce the pollutant in Kali Buntung’s downstream.